2020
DOI: 10.4149/km_2019_4_219
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution of fibre laser welded TRIP and HSLA steel sheets with different thicknesses

Abstract: The microstructure of fibre laser welded joint of TRIP 690T and HSLA LAD340 steel sheets with different thicknesses was evaluated. The microstructure in the fusion zone was built of martensite, lower bainite and a small portion of upper bainite. Martensite and lower bainite created in both the coarse-grained and fine-grained heat affected zones (HAZs) near 690T steel, but some portion of ferrite was also identified in the fine-grained HAZ near 690T steel. Acicular ferrite, upper bainite, and equiaxed ferrite w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…They found that the microstructure of the weld zone is martensite, and the microstructure is the mixture of martensite, bainite and ferrite on both sides of HAZ, which also has observed in this paper (show in figures 8-10). Sevc [32] has investigated the fiber laser welded TRIP/HLSA sheets with different thicknesses, they found that the highest microhardness is at the HAZ of TRIP steel side, while in this study, the higher microhardness is at the weld center, which also agrees with our research result (show in figure 11). Rahul [18] has investigated on the effect of power and velocity of laser beam welding on tensile strength of the TRIP steel butt weld joint, and Shu [33] has also studied the effect of process parameters on the tensile strength of the laser welded joint of HC550/DP780 high strength steel with different thicknesses.…”
Section: Effect Of Welding Speed On the Mechanical Properties Of Weldsupporting
confidence: 92%
“…They found that the microstructure of the weld zone is martensite, and the microstructure is the mixture of martensite, bainite and ferrite on both sides of HAZ, which also has observed in this paper (show in figures 8-10). Sevc [32] has investigated the fiber laser welded TRIP/HLSA sheets with different thicknesses, they found that the highest microhardness is at the HAZ of TRIP steel side, while in this study, the higher microhardness is at the weld center, which also agrees with our research result (show in figure 11). Rahul [18] has investigated on the effect of power and velocity of laser beam welding on tensile strength of the TRIP steel butt weld joint, and Shu [33] has also studied the effect of process parameters on the tensile strength of the laser welded joint of HC550/DP780 high strength steel with different thicknesses.…”
Section: Effect Of Welding Speed On the Mechanical Properties Of Weldsupporting
confidence: 92%
“…The ferrite portion increased with the distance from the weld centre and with a decrease in the maximal temperature achieved during the welding cycle in the inter-critical temperature interval. The smallest value of 214 HV 0.1 in the HAZ of TRIP690 steel was in the vicinity of TRIP690 steel BM and represented the softening region of sub-critical HAZ [27]. From the information above, it is obvious that significant differences can be found when describing the microstructure in HAZs of CP and TRIP steel grades.…”
Section: Introductionmentioning
confidence: 95%
“…Acicular cementite, massive ferrite, layered pearlite, and granular bainite were mainly observed in the joint [19]. In the work [27], TRIP690 and 340LAD steel were fibre laser welded. The microstructure in the coarse-grained HAZ of TRIP690 steel was built mainly of martensite and lower bainite with a maximal hardness of 457 HV 0.1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure and properties of laser-welded TRIP steel joints have previously been studied [5][6][7][8][9]. For instance, P. VEC [10] found that the weld zone structure of the laser-welded joint of TRIP690T steel is martensite, lower bainite, and a small amount of upper bainite. Furthermore, the fine grain zone near TRIP690T steel is martensite, lower bainite, and ferrite.…”
Section: Introductionmentioning
confidence: 99%